Survey on The Impact of Road Transportation Companies on Travel Motivations in Nigeria Geo-Political Zones - Echeta Sydney c (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2023)
This research survey on the impact of Road Transport Companies on travel Motivations in Nigeria Geo-political zones. Transport by road is the physical process of transporting cargo or people by road using motor vehicles or other means such as bicycles motorcycles etc, Travel motivations are the inner state of a person or certain needs and wants of the tourists or people that can be considered as one of the most important psychological influences of behavior. However, a lot of Researchers have confirmed that many people are motivated to travel due to the existing road transport Companies and road transport Companies don't know much about their existence in terms of motivations. The specific objectives examined the effect of Road transport companies on Tourist social interactions, cultural traveling, and traveling for pleasure. A lot of people will also benefit from this research including Future researchers, travelers, and transport companies. The method of data collection used in this research study was primary data which was achieved through questionnaires, Finding shows that there is a strong relationship between Road transport companies and tourist traveling for social interactions, cultural purpose, and pleasure. The researcher concludes that road transport companies play a positive role in motivating tourist/travelers for traveling and recommend that the government of the day should provide good Road for these transport Companies Since tourist sites are more in the rural communities and Road transport companies should train more for the drivers and customer attendants.